2021
DOI: 10.3390/molecules26082303
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Drug Metformin and MCL1 Inhibitor S63845 Exhibit Anticancer Activity in Myeloid Leukemia Cells via Redox Remodeling

Abstract: Metabolic landscape and sensitivity to apoptosis induction play a crucial role in acute myeloid leukemia (AML) resistance. Therefore, we investigated the effect of metformin, a medication that also acts as an inhibitor of oxidative phosphorylation (OXPHOS), and MCL-1 inhibitor S63845 in AML cell lines NB4, KG1 and chemoresistant KG1A cells. The impact of compounds was evaluated using fluorescence-based metabolic flux analysis, assessment of mitochondrial Δψ and cellular ROS, trypan blue exclusion, Annexin V-PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…It was also suggested that this agent can protect against oxidative stressinduced cell death. 21,22 In the present study, we observed that TOS and OSI values decreased significantly along with metformin treatment, whereas TAS increased, although not significantly.…”
Section: Discussionsupporting
confidence: 44%
“…It was also suggested that this agent can protect against oxidative stressinduced cell death. 21,22 In the present study, we observed that TOS and OSI values decreased significantly along with metformin treatment, whereas TAS increased, although not significantly.…”
Section: Discussionsupporting
confidence: 44%
“…Loss of MMP in response to S63845 was also reported in DLBCL and AML cells [ 35 , 38 ]. To date, ROS have not been investigated in most lymphoma studies, but their induction was also found in two AML cell lines at 24 h in response to S63845 [ 39 ]. Thus, as resistant CTCL cell lines were completely lacking caspase activation as well as loss of MMP and ROS production in response to S63845, the causes of their resistance had to be sought more above in the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, substantial evidence indicated that the remodeling redox status of metformin is relevant to different types of cancer. The apoptosis of acute myeloid leukemia (AML) cells is observed after treatment with metformin, which is mediated by reducing ROS via downregulation of oxidative phosphorylation (OXPHOS) [100]. The proliferation of pancreatic cells and osteosarcoma is also inhibited by metformin-mediated ROS downregulation [101,102].…”
Section: Metformin Exerts Its Effect In An Ampk-independent Manner Me...mentioning
confidence: 99%